Insights into liquid phase sintering mechanism of high-alumina and low-silica hematite ores - Wanlong Fan; Zhiwei Peng; Tuo Pan; Huibo Liu; Shaochang Nie; Lin Xiong; Qiang Zhong; Mingjun Rao (Minerals Engineering, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Iron ores with contrasting redox properties drive iron biogeochemical cycling to enhance acesulfame and nutrients removal in constructed wetlands - Mingjun Li; Zhiyi Lin; Peihao Yan; Tianzhi Lan; Jian Zhang; Huijun Xie; Haiming Wu (Journal of Hazardous Materials, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Molecular insights into whey protein fibril-sodium alginate-piperine complexes for stabilizing astaxanthin emulsions with improved bioaccessibility - Junquan Zheng; Daobang Tang; Xueming Liu; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Jingrong Cheng (Food Hydrocolloids, 2026)

Quality optimization and shelf-life prediction of braised beef using synergistic ε-polylysine-integrated sterilization technologies - Jingrong Cheng; Zhenhua Shi; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Food Control, 2026)

Enhanced stability and bioavailability of astaxanthin via piperine co-encapsulation in whey protein fibril- sodium alginate complexes - Jingrong Cheng; Junquan Zheng; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Carbohydrate Polymers, 2026)

A high-accuracy stacking model for automatic identification of aeolian saltating tracks in high-speed pictures - Mengjie Pu; Fanmin Mei; Chuan Lin; Mingjun Sui; Hongda Chen; Shenyang He; Weikai Wang; Chang Zhou; Jin Su; Jinguang Chen (Aeolian Research, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Salicylic acid as a pathway inducer for improved bioremediation of oil-polluted saline-alkali soils by chemotactic S. Stutzeri M3 - Lin Li; Xiaoying Yu; Mingjun Wang; Huaji Sun; Jingyi Zhu; Xuehan Wang; Shuiquan Chen; Shugang Hu (Bioresource Technology, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Storm water management model simulations of the non-point source pollution load in the northern Anhui plain - Yun Wan; Mingjun Li; Nan Zhang; Mengwan Lin; Yuxuan Li; Peiqing Huang; Yuqi Feng; Bai Sun; Wei Wei; Shuguang Zhu (Ecohydrology & Hydrobiology, 2025)

Rapid visual field detection of Pratylenchus coffeae in yam tissues via RPA-CRISPR/Cas12a - Weichao Zhao; Mengli Lin; Yulong He; Jin Gao; Jiangli Zhang; Mingjun Li; Qingxiang Yang (Crop Protection, 2025)

Scenario-based forecasting and multi-objective optimization of low-carbon pathways: A perspective on the composition and carbon emission inventory of urban water treatment plants - Hui Tao; Lin Wang; Mingjun Sheng; Yan Zhang; Qixuan Zhu; Ziyi Li; Tao Lin (Journal of Water Process Engineering, 2025)

Synchronous removal of heavy metals and ammonia-nitrogen by magnesium ammonium phosphate (MAP)-enhanced microbial induced calcite precipitation (MICP) - Lin Li; Huaji Sun; Chongyang Ren; Ziyi Zhao; Yueteng Song; Mingjun Wang; Shuiquan Chen; Gang Zhou (Journal of Hazardous Materials, 2025)

Double-confined FeCo nanoalloys as efficient and stable catalyst for selective hydrogenation of nitroarenes - Zhenyu Lei; Hao Sun; Lin Wu; Honglei Sun; Xiaomin Yang; Jingyao Liu; Peng Zhang; Mingjun Jia (Chemical Engineering Journal, 2025)

Enhanced mineralization and dust suppression mechanism of Bacillus pasteurii synergized with Bacillus mucilaginosus capable of CO2 capture effect - Gang Zhou; Ziyi Zhao; Guoqing Zhang; Xiao Gao; Mingjun Wang; Bo Wei; Xi Chen; Jihua Li; Lin Li (Chemical Engineering Journal, 2025)

Constructed wetlands for wastewater treatment and reuse: Two decades of experience from China - Zhiyi Lin; Mingjun Li; Peihao Yan; Jian Zhang; Huijun Xie; Haiming Wu (Environmental Research, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Characterization and functional analysis of small heat shock protein gene HSP20.1 in Bombyx mandarina - Hui An; Jiaqi Ding; Enxi Chen; Ruonan Li; Mingjun Lin; Heying Qian; Guodong Zhao (International Journal of Tropical Insect Science, 2024)

Refining habitat selection for sulfate-reducing bacteria: Evaluating suitability and adaptability for sulfate-metal wastewater treatment during anaerobic-to-aerobic transitions - Zhendong Yang; Jing Wang; Qihong Wu; Zhaoyue Yang; Tuan Liu; Li Zeng; Zhaogang Lin; Mingjun Li; I.A. Ibrahim; Huaqun Yin; Zhenghua Liu (Journal of Environmental Management, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Association of NID2 SNPs with Glioma Risk and Prognosis in the Chinese Population - Jie Hao; Congmei Huang; Weiwei Zhao; Lin Zhao; Xiuxia Hu; WenJie Zhang; Le Guo; Xia Dou; Tianbo Jin; Mingjun Hu (NeuroMolecular Medicine, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

A self-healing electrocatalyst for manganese-based flow battery - Mingjun Nan; Min Wu; Zichao Zhao; Lin Qiao; Huamin Zhang; Xiangkun Ma (Chemical Engineering Journal, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

Assessing nutritional and economic aspects of food loss and waste in China - Ruigang Wang; Shijun Lu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Mingjun Zhao; Guangyan Cheng (Sustainable Production and Consumption, 2023)

EIF4A3-Induced Exosomal circLRRC8A Alleviates Granulosa Cells Senescence Via the miR-125a-3p/NFE2L1 axis - Jie Xing; Mengxue Zhang; Shijie Zhao; Mingjun Lu; Li Lin; Lu Chen; Wujiang Gao; Wenxin Li; Junyu Shang; Jiamin Zhou; Xiaolan Zhu (Stem Cell Reviews and Reports, 2023)
Premature ovarian failure (POF) is an important cause of female infertility and seriously impacts the physical and psychological health of patients. Mesenchymal stromal cells-derived exosomes (MSCs-Exos) have an essential role in the treatment of reproductive disorders, particularly POF. However, the biological function and therapeutic mechanism of MSCs exosomal circRNAs in POF remain to be determined. Here, with bioinformatics analysis and functional assays, circLRRC8A was found to be downregulated in senescent granulosa cells (GCs) and acted as a crucial factor in MSCs-Exos for oxidative damage protection and anti-senescence of GCs in vitro and in vivo. Mechanistic investigations revealed that circLRRC8A served as an endogenous miR-125a-3p sponge to downregulate NFE2L1 expression. Moreover, eukaryotic initiation factor 4A3 (EIF4A3), acting as a pre-mRNA splicing factor, promoted circLRRC8A cyclization and expression by directly binding to the LRRC8A mRNA transcript. Notably, EIF4A3 silencing reduced circLRRC8A expression and attenuated the therapeutic effect of MSCs-Exos on oxidatively damaged GCs. This study demonstrates a new therapeutic pathway for cellular senescence protection against oxidative damage by delivering circLRRC8A-enriched exosomes through the circLRRC8A/miR-125a-3p/NFE2L1 axis and paves the way for the establishment of a cell-free therapeutic approach for POF. CircLRRC8A may be a promising circulating biomarker for diagnosis and prognosis and an exceptional candidate for further therapeutic exploration. Graphical Abstract

Manganese-based flow battery based on the MnCl2 electrolyte for energy storage - Yuqin Liu; Mingjun Nan; Zichao Zhao; Bo Shen; Lin Qiao; Huamin Zhang; Xiangkun Ma (Chemical Engineering Journal, 2023)

Quantifying food loss along the animal products supply chain in China with large-scale field-survey based primary data - Ruigang Wang; Gang Liu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Shijun Lu; Mingjun Zhao; Huiwu Sun; Chuang Ma; Guangyan Cheng (Resources, Conservation and Recycling, 2023)

Effectiveness of cascading time series models based on meteorological factors in improving health risk prediction - Shuopeng Jia; Weibin She; Zhipeng Pi; Buying Niu; Jinhua Zhang; Xihan Lin; Mingjun Xu; Weiya She; Jun Liao (Environmental Science and Pollution Research, 2022)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Differential antigen expression between human eccrine sweat glands and hair follicles/pilosebaceous units - Leilei Cao; Liyun Chen; Haihong Li; Zairong Wei; Sitian Xie; Mingjun Zhang; Yao Lin; Haihua Huang (Journal of Molecular Histology, 2019)

Three-dimensional reconstructed eccrine sweat glands with vascularization and cholinergic and adrenergic innervation - Mingjun Zhang; Haihong Li; Liyun Chen; Shuhua Fang; Sitian Xie; Changmin Lin (Journal of Molecular Histology, 2018)

Characterization of the Zhikong Scallop (Chlamys farreri) Mantle Transcriptome and Identification of Biomineralization-Related Genes - Mingjun Shi; Ya Lin; Guangrui Xu; Liping Xie; Xiaoli Hu; Zhenmin Bao; Rongqing Zhang (Marine Biotechnology, 2013)

Vegetation change in the Mt. Qomolangma Nature Reserve from 1981 to 2001 - Wei Zhang; Yili Zhang; Zhaofeng Wang; Mingjun Ding; Xuchao Yang; Xuedong Lin; Linshan Liu (Journal of Geographical Sciences, 2007)